Fulminant Leptospirosis: an autopsy case - de Campos, Fernando Peixoto Ferraz; Simões, Angélica Braz (Autopsy and Case Reports, 2011)
Leptospirosis is an acute febrile illness affecting humans and/or animals, with a high global incidence mainly in the tropical developing countries. Outbreaks are frequently related to rainy season, floods and the presence of reservoirs animals more commonly rodents and dogs. The disease occurs in the rural and urban areas linked to some occupational and recreational activities. The younger population is at higher risk of infection. Approximately 5% - 15% of the patients develop the severemanifestations of the disease known as Weill’s disease that can be associated with leptospirosis pulmonary hemorrhage syndrome. We present an autopsy case of an octogenarian patient, resident of the urban area of the city of São Paulo, admitted to the Hospital Universitário da Universidade de São Paulo, who presented a fulminant outcome. The autopsy revealed pulmonary involvement characterized by diffuse alveolar hemorrhage and interstitial mononuclear infiltration. The liver histology presented disorganization of the liver cell plates, congested sinusoids and Kupfer cells hyperplasia. Acute tubular necrosis and interstitial nephritis was the hallmark of kidneys involvment.